2004
DOI: 10.1051/forest:2004081
|View full text |Cite
|
Sign up to set email alerts
|

Micrografting of mature stone pine (Pinus pinea L.) trees

Abstract: -This paper describes an in vitro micrografting method for selected mature Pinus pinea L. trees. Needle fascicles of five selected clones were micrografted onto hypocotyls of two weeks-old germinated isolated embryos. Fascicle meristems outgrowth was recorded after one month of culture and the performance of the clones assayed was evaluated. Clones behave statistically different in establishment and development rates. Overall success of our protocol reached 43% of the graftings made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 7 publications
1
22
0
1
Order By: Relevance
“…The decrease in vigor and adventitious organs formation capacity are responses associated with the tissue maturation stage [4]. Hence, basal scions must present higher morphogenic capacities than apical ones, because their younger ontogenetic age determined by the proximity to the mother cell located at the collar of the ortet [5] [6]. In the consolidation phase we found that juvenile traits of ontogenically young tissues can be preserved in basal scions.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…The decrease in vigor and adventitious organs formation capacity are responses associated with the tissue maturation stage [4]. Hence, basal scions must present higher morphogenic capacities than apical ones, because their younger ontogenetic age determined by the proximity to the mother cell located at the collar of the ortet [5] [6]. In the consolidation phase we found that juvenile traits of ontogenically young tissues can be preserved in basal scions.…”
Section: Resultsmentioning
confidence: 61%
“…This higher photochemical activity is a proxy of higher CO 2 assimilation capacity, and therefore of greater photosynthetic performance and potentially faster growth [18] [20] [21]. Additionally higher Fv/Fm reflects an ontogenetic age gradient of shoot tips morphogenic competence, where basal meristematic shoot tips present higher morphogenic capacities than apical ones [5] [6]. Finally, based on our results, we conclude that Fv/Fm can be an indicator of the micrograft's development according to the shoot tips position in the ortet and can be a useful indicator of the physiological stage of scions during micrograft transition from establishment to consolidation.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Antepfıstığının Siirt çeşidiyle ilgili ana bitkilerden alınma zamanlarına göre elde edilen başarının Nisan %70, Haziran %80 olduğu, bunun aksine Şubat ayı içerisinde alınan eksplantlardaki aşı başarısının %10 olduğu bildirilmiştir (Onay ve ark., 2004). Fıstık çamı ve monteri çamı bitkilerde yapılan aşılamalarda mevsimsel değişim açısından en iyi aşı başarısı bitkilerin kış dinlenme periyodunda alınan eksplantlarından elde edilmiştir (Fraga et al, 2002;Cortizo et al, 2004). Dinlenme halindeki sürgünlerde daha iyi aşı başarısı sağlanan türler olmakla birlikte; bunun aksine aktif gelişme döneminde daha iyi sonuç veren türlerde bulunmaktadır.…”
Section: Fizyolojik Koşullarunclassified